The Lintner-Butters Analysis of the Effect of Mergers on Industrial Concentration, 1940-1947: A Reply - Blair, John M.; Houghton, Harrison F. (The Review of Economics and Statistics, 1951)
John M. Blair, Harrison F. Houghton, The Lintner-Butters Analysis of the Effect of Mergers on Industrial Concentration, 1940-1947: A Reply, The Review of Economics and Statistics, Vol. 33, No. 1 (Feb., 1951), pp. 63-67